Implementasi Media Interaktif Articulate Storyline 3 dalam Meningkatkan Keterampilan Menulis Arab Siswa Madrasah Aliyah - Saskiyah, Bela Alimatus; Hasyim, Mochamad; Nurrokhmatulloh, Nurrokhmatulloh (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to improve the writing skills of Madrasah Aliyah Tutur students by implementing innovative and effective Articulate Storyline 3 interactive media. Using the Classroom Action Research (CAR) method for two cycles, this study involved all XI grade MA Ya Ikhsan Tutur students, totaling 25 students. The research instruments used included observation sheets and learning outcome tests to measure the improvement of learning outcomes and N-gain analysis to determine the improvement of students' interest in learning. The results showed significant improvement: student learning outcomes increased from 40% in the first cycle to 80% in the second cycle, while student interest in learning increased from 56% to 88%. This research introduces novelty in using Articulate Storyline 3 interactive media in Arabic subjects, which previously focused on other subjects. The results of this study indicate that Articulate Storyline 3 interactive media can be an effective alternative in improving students' learning outcomes and interest in Arabic language learning, thus improving the quality of learning in schools.